Using a Media Campaign to Increase Engagement With a Mobile-Based Youth Smoking Cessation Program. Issue 5 (June 2018) - Sanders, Amy; Robinson, Cendrine; Taylor, Shani C.; Post, Samantha D.; Goldfarb, Jeffrey; Shi, Rui; Hunt, Yvonne M.; Augustson, Erik M.
Purpose: To describe the impact of the National Cancer Institute's promotion of its youth smoking cessation program, Smokefree Teen (SFT). Design: We provide a description of campaign strategies and outcomes as a means to engage a teen audience in cessation resources using a cost-effective approach. Setting: The campaign occurred nationally, using traditional (TV and radio), online, and social media outreach. Participants: Ads targeted adolescent smokers (aged 14-17). The baseline population was 42 586 and increased to 464 357 during the campaign. Measures: Metrics used to assess outcomes include (1) visits to SFT website from traditional and online ads, (2) cost to get an online ad clicked (cost-per-click), and (3) SmokefreeTXT program enrollments during the 8-week campaign period. Analysis: We conducted a quantitative performance review of all tactics. Results: The SFT campaign achieved an online ad click-through rate of 0.33%, exceeding industry averages of 0.15%. Overall, web traffic toteen.smokefree.gov increased by 980%, and the online cost-per-click for ads, including social media actions, was approximately $1 as compared with $107 for traditional ads. Additionally, the campaign increased the SmokefreeTXT program teen sign-ups by 1334%. Conclusion: The campaign increased engagement with evidence-informed cessation resources for teen smokers. Results show the potential of using multiple, online channels to help increase engagement with core resources.